2018
DOI: 10.1021/acs.joc.8b00238
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Reaction Cascade from O-Pent-4-enyl-Substituted Salicylates to Complex Multifunctional Scaffolds

Abstract: The arene ring of the title compounds is cleaved by a reaction cascade which is initiated by an intramolecular ortho photocycloaddition reaction. Tricyclic products were obtained in a highly regio- and diastereoselective fashion via a cyclooctatriene intermediate. The facial diastereoselectivity exerted by a stereogenic center in the tether is moderate to good (dr = 65/35 to 82/18). Yields were acceptable (44-87%) except for a single substrate which had a geminal dimethyl substitution in the tether and which g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…With 4 in hand, we focused on the key step of our synthetic strategy, the photochemical reaction cascade furnishing the protoilludane core. Previous experiments 11,12,14 had shown that the desired photochemical transformation proceeds efficiently in freshly distilled dry methanol as the solvent (0.1 mΜ) and with irradiation at  = 300 or 350 nm. We were pleased to detect reasonably good conversions of 4 after irradiation at  = 300 and 350 nm for two hours ( Table 1, entries 1 and 2, respectively).…”
Section: Homentioning
confidence: 99%
See 1 more Smart Citation
“…With 4 in hand, we focused on the key step of our synthetic strategy, the photochemical reaction cascade furnishing the protoilludane core. Previous experiments 11,12,14 had shown that the desired photochemical transformation proceeds efficiently in freshly distilled dry methanol as the solvent (0.1 mΜ) and with irradiation at  = 300 or 350 nm. We were pleased to detect reasonably good conversions of 4 after irradiation at  = 300 and 350 nm for two hours ( Table 1, entries 1 and 2, respectively).…”
Section: Homentioning
confidence: 99%
“…5a,9 In their pioneering work, Johnson and Vollhardt accomplished a total synthesis of illudol (2) through [2+2+2]cycloaddition of an enediyne precursor. 10 Our synthetic approach was based on our recently reported work, 11,12 in the course of which we had found that certain indanone substrates B undergo an unprecedented B → E → F intramolecular photochemical transformation (Scheme 1). This key step allowed us to access the protoilludane core E in a single operation.…”
mentioning
confidence: 99%
“…Notable photochemical strategies [8] to secure formation of the four-membered ring include the common [2+ +2] photocycloaddition [9] but also some less frequently used methods such as the photochemical 1,3-acyl shift reaction of b,g-unsaturated enones. [10] Our interest in protoilludanes was triggered by recent work [11] on ar eaction cascade [12] that is initiated by an ortho photocycloaddition and that generates the bicyclo[4.2.0]octane skeleton, acore element of structure A,inasingle operation. Herein, we disclose aconcise access to protoilludane sesquiterpenes that culminated in the first total synthesis of atlanticone C( 1)a nd in the stereoselective synthesis of two other advanced intermediates that had been previously converted into D 6 -protoilludene (2)a nd paesslerin A( 3).Arenes B (Scheme 1), which have ac arbonyl group in ortho position to an alkenyloxy group,are known to undergo an initial [2+ +2] photocycloadditon at the arene (ortho photocycloaddition [13,14] ).…”
mentioning
confidence: 99%
“…[11] Given the structural similarity of E with the biyclo[4.2.0]cyclooctane part of structure A,w er easoned that as ubstituent Y = O would facilitate aring opening of the former tether and would secure the introduction of the hydroxy group required at position C-13 of the natural product atlanticone C. Regarding the other variable Ri ns tructure E,alate-stage introduction of the C-12 methyl group did not seem feasible.I tw as thus mandatory to introduce this substituent already in the starting material, that is,i nto the meta position of the salicylate.T he respective salicylic acid is readily available through aK olbe-Schmitt reaction, [18] and substrate 4b (Scheme 2) was synthesized in three steps and an overall yield of 77 %f rom paracresol (see the Supporting Information). Ther esults of its photochemical reaction were disappointing,h owever.W hile the unsubstituted salicylate 4a had given the desired product 5ain 65 %yield in previous work, [11] substrate 4bdelivered an inseparable mixture of diastereoisomers in only 46 %y ield under identical reaction conditions with astrict preference for the opposite regioisomer.A ttempts to alter this reaction outcome by changing the light source or the solvent remained unsuccessful. Apparently,alarger Rgroup (R = Me instead of R = H) avoids the sterically encumbered position at the quaternary carbon center and the [4p]r ing closure to the linear product 5b' ' becomes competitive.Inspection of molecular models indicated that ac yclic carbonyl compound, that is,aketone,m ight enforce the desired reaction pathway,delivering aproduct E with an even higher structural similarity to skeleton A.However,there was no precedence for the ortho photocycloaddition of cyclic aromatic ketones,a nd many photochemical reaction pathways are conceivable for the keto group both in ap otential substrate and its product.…”
mentioning
confidence: 99%
“…[16] Following up on earlier work by Wagner and co-workers, [17] we have recently found that several salicylates and salicyclic acid derivatives deliver clean formation of products E if irradiated at l = 300 nm in methanol solution. [11] Given the structural similarity of E with the biyclo[4.2.0]cyclooctane part of structure A,w er easoned that as ubstituent Y = O would facilitate aring opening of the former tether and would secure the introduction of the hydroxy group required at position C-13 of the natural product atlanticone C. Regarding the other variable Ri ns tructure E,alate-stage introduction of the C-12 methyl group did not seem feasible.I tw as thus mandatory to introduce this substituent already in the starting material, that is,i nto the meta position of the salicylate.T he respective salicylic acid is readily available through aK olbe-Schmitt reaction, [18] and substrate 4b (Scheme 2) was synthesized in three steps and an overall yield of 77 %f rom paracresol (see the Supporting Information). Ther esults of its photochemical reaction were disappointing,h owever.W hile the unsubstituted salicylate 4a had given the desired product 5ain 65 %yield in previous work, [11] substrate 4bdelivered an inseparable mixture of diastereoisomers in only 46 %y ield under identical reaction conditions with astrict preference for the opposite regioisomer.A ttempts to alter this reaction outcome by changing the light source or the solvent remained unsuccessful.…”
mentioning
confidence: 99%